Anti‐early endosome antigen 1 autoantibodies were detected in a pemphigus‐like patient but not in the majority of pemphigus diseases. Issue 5 (May 2016) - Nishikawa, Ryuhei; Takahashi, Hitoshi; Matsuda, Mitsuhiro; Imaoka, Kaoru; Ogawa, Masahiro; Teye, Kwesi; Tsuchisaka, Atsunari; Koga, Hiroshi; Komorowski, Lars; Probst, Christian; Hachiya, Takahisa; Fritzler, Marvin J.; et al.
Abstract: Although the major autoantigens in classic pemphigus are desmogleins, sera from various types of pemphigus react with a number of other molecules, including desmocollins and plakin proteins. However, other novel pemphigus‐related autoantigens remain to be identified. In this study, i mmunoblotting for serum from an atypical autoimmune bullous disease patient identified an unknown 175 kDa protein. Subsequent studies using two‐dimensional gel electrophoresis, immunoblotting and mass‐spectrometry identified the 175 kDa protein as early endosome antigen 1 (EEA1). This finding was confirmed by subsequent immunological studies, including indirect immunofluorescence of skin and cultured keratinocytes, two‐dimensional gel electrophoresis and immunoblotting with anti‐EEA1 polyclonal antibody, and preabsorption with EEA1 recombinant protein. Finally, we developed a novel BIOCHIP assay using full‐length EEA1 recombinant protein to detect anti‐EEA1 antibodies. However, none of 35 sera from various types of pemphigus showed anti‐EEA1 antibodies in the BIOCHIP assay, with the exception of the serum from the index case. In addition, various findings in the index case did not suggest pathogenic role of anti‐EEA1 autoantibodies. Therefore, although we successfully identified the 175 kDa protein reacted by a serum of an atypical pemphigus‐like patient as EEA1, novel BIOCHIP study for other pemphigus sera indicated that EEA1 is not a common and pathogenic autoantigen in pemphigus.